The Impact of Rural Tourism on the Economic Growth of Rural Residents in Bangladesh: A Study on Melandaha Upazila in Jamalpur District - Islam, Nora (European Scientific Journal, ESJ, 2023)
The development of rural tourism can contribute to both socio-economic development and environmental benefits for the people within rural areas. It plays a vital role in society, fostering business growth, generating employment, and ensuring a better livelihood for rural inhabitants. Bangladesh is a land of natural beauty. Melandaha Upazila in Jamalpur District is a hidden treasure of natural beauties, enriched with colorful rural life, archaeological and historical sites, and cultural attraction. With proper care, this location could emerge as a prominent rural tourism destination in Bangladesh. This paper focuses on recognizing how rural tourism can be the best alternative of earning for rural people to minimize the dependency on seasonal work (e.g., agriculture, fishing, boating), create alternative sources of income, and ensure economic development as well as solvency through participation in rural tourism businesses. This study was undertaken to explore a secondary income source for rural people who depend on an agricultural-based economy. To test this assumption, a survey questionnaire was administered to identify whether the commencement of rural tourism can stimulate the economic growth of rural residents or not. This study identifies the major attractions and prospects of the rural tourism in this destination. Finally, this study also presents a SWOT analysis and suggests necessary recommendations for commencing rural tourism in Melandaha Upazilla.